Pacient Specific Instruments (PSI) při implantaci TEP kolenního kloubu - roční výsledky prospektivní randomizované studie - Musil, David; Stehlík, Jiří; Abrman, Kristián; Held, Martin; Sadovský, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY The aim of this prospective study was to evaluate, at one year of follow-up, radiographic and clinical results of total knee arthroplasty (TKA) performed with use of Zimmer® Patient Specific Instruments (PSIs) which allow for planning and customising each patient's TKA. MATERIAL AND METHODS Of the patients with knee arthritis who were eligible for joint replacement, 23 were randomly selected and included in this study. There were 11 men and 12 women, with 11 right and 12 left knee joints. On the basis of pre-operative CT scans, PSI custom-made pin guides, which conformed to the individual patient's anatomy, were produced and then used in the THA surgery involving a NexGen (CR) system. All patients were examined before surgery and at 1 year after THA. The evaluation at a follow-up visit included standing full-length radiographs (antero-posterior and lateral), Knee Score results, range of motion (ROM), patient's satisfaction report, and post-operative complications. The X-ray views were examined for mechanical leg axis alignment, TKA alignment in antero-posterior and lateral projection and signs of potential loosening. RESULTS At 1 post-operative year, the average Knee Society Score (KSS) was 85.5 points and the average functional score was 82.6 point. The satisfaction rate was 94% and, on a school rating system, the average mark was 1.3. The average postoperative ROM value was 116°. All patients were willing to undergo the surgery again. The only complication was thrombosis in one patient. Radiographic findings of knee alignment were optimal in 18, correct (up to 3° deviation) in three and incorrect (above 3° deviation) in two patients. Radiographic signs of loosening were not recorded. DISCUSSION Correct knee alignment is one of the requirements for achieving a good TKA outcome. Various techniques are used to improve the total knee process (computer-aided surgery, customised guides). Zimmer Patient Specific Instruments provide advanced pre-operative planning and more accurate implant sizing and alignment. An experienced surgeon can achieve the same good results with conventional planning under standard conditions but the use of PSIs is clearly more beneficial in patients with extra-articular deformities and in patients in whom femoral intramedullary guides cannot be employed. To produce a custom-made pin guide requires a CT scan of the whole leg and is also associated with additional paperwork. The PSIs simplify the total knee process from start to finish and surgeons have complete flexibility to make fine-tuning adjustments during the procedure. CONCLUSIONS Zimmer Patient Specific Instruments allow for exact alignment of both the femoral and the tibial component in a TKA process. Under standard circumstances, clinical and radiographic outcomes are comparable with those of conventional planning. However, the use of PSIs is clearly more beneficial in patients with extra-articular deformities and in patients in whom femoral intramedullary guides cannot be employed. KEY WORDS: total knee arthroplasty, TKA, Patient Specific Instruments, PSIs.
Keywords: Prospective Studies; Tomography, X-Ray Computed; Humans; totální endoprotéza kolene; následné studie; prospektivní studie; Follow-Up Studies; mužské pohlaví; kolenní kloub; Knee Joint; výsledek terapie; Arthroplasty, Replacement, Knee; Treatment Outcome; ženské pohlaví; lidé; artritida; Arthritis; počítačová rentgenová tomografie; Male; Female